Atlas of diagnostic hematology - Salama, Mohamed E.; Teruya-Feldstein, Julie; Kremyanskaya, Marina (Philadelphia: Elsevier, 2021)
"Ideal as a quick, easy-to-use reference in the laboratory or clinical setting, Atlas of Diagnostic Hematology is an abundantly illustrated guide to the vast range of malignant and non-malignant disorders of the blood. More than 1,200 vibrant, full-color images enable you to identify and compare the unique clinical and histologic features of various blood disorders and confidently reach a diagnosis. Coverage includes photos of actual cases that span the entire range of this complex field, including rare conditions and difficult diagnoses"--Publisher's description.
Bibliographies References and Index.
Keywords: Hematology; Thalassemia